Potencial de Zophobas morio en la inclusión de planes de alimentación de centros de conservación de fauna silvestre - Torres Gutiérrez, Juan Sebastián (2024)
The aim of this study was to evaluate the inclusion of the beetle Zophoba morio in Rattus norvegicus diets. The work was carried out in the bioterium of the Wakata Biopark, located in the municipality of Tocancipa, Colombia. Sixteen weaned rats were randomly assigned to two groups: control fed with commercial feed and experimental with inclusion of 20% Zophobas and 60% commercial feed for 30 days. Nutritional quality, consumption, weight gain, feed conversion factor and feed conversion efficiency were determined. A completely randomized design was used. A higher percentage of crude protein (p=0.0012) and ether extract (p=0.0080) was found in the zophobas larvae, while the percentage of ash was higher in the feed (p=0.0398). A higher consumption (p=0.0110) was found in the control group. There were no significant differences between groups or by sex in weight gain, feed conversion ratio or feed conversion efficiency. Zophoba morio larvae is a promising resource for inclusion in diets to produce Rattus norvegicus in conservation centres.